Bycatch reduction in the Norwegian deep-water shrimp (Pandalus borealis) fishery with a double grid selection system - Larsen, Roger B.; Herrmann, Bent; Sistiaga, Manu Berrondo; Brinkhof, Jesse; Grimaldo, Eduardo (Fisheries Research, 2018)
Source at https://doi.org/10.1016/j.fishres.2018.08.007 . Licensed CC BY NC ND Trawlers targeting Deep-water Shrimp ( Pandalus borealis ) in the North Atlantic use a Nordmøre sorting grid ahead of a small-meshed codend. Based on experimental fishing, the effect of adding a 9 mm spaced release grid behind the mandatory 19 mm spaced Nordmøre sorting grid, was determined. The performance in terms of size selection of the release grid and the two grids combined were assessed for target Deep-water Shrimp and for juvenile Redfish ( Sebastes spp.) and American Plaice ( Hippoglossoides platessoides ), two of the most common bycatch species in the fishery. The aim of using the release grid was to improve the escape of undersized shrimp and the bycatch of juvenile fish from the gear. The results demonstrated that the release grid improved the escape of the smallest Deep-water Shrimp significantly. The fraction of small shrimp released through this grid was estimated to be 45%. However, the results also revealed the need for further improvements in the design of the release grid to increase the reduction of small shrimp and juvenile fish bycatch. For Redfish and American Plaice the fractions of juveniles escaping through the release grid were estimated to be 16% and 32%, respectively. In addition, the release grid only led to the escape of the smallest juvenile individuals, in particular for Redfish.